A Preliminary Study on Testing the Compressive Strength of Sleeve Grouting Material Based on the Leeb Hardness Method. Issue 1 (January 2021) - Ding, Chenchen; Gu, Sheng; Yuan, Yiwei; Wu, Yulong
Abstract: In order to explore the feasibility of testing the compressive strength of sleeve grouting material in practical engineering by the Leeb hardness method, we made 12 groups of standard specimens out of grouting material, analyze the correlation between surface hardness and compressive strength of grouting material by experiments. Experimental results show that, The surface hardness test results of the sleeve grouting material are in accordance with the normal distribution. With the guarantee rate of 95%, eliminating the extreme value in the hardness test data can significantly reduce the discreteness of the data and improve the accuracy of the calculation results. There is a significant correlation between surface hardness and compressive strength of grouting material, the best fitting effect is by using exponential function, the average relative error is 7.45%, the relative standard deviation is 8.61% and the correlation coefficient is 0.864. The experimental results provide a reference for testing the compressive strength of sleeve grouting material by the Leeb hardness method.